2017
DOI: 10.1021/acsami.6b16194
|View full text |Cite
|
Sign up to set email alerts
|

Simple and Facile Approach To Create Charge Reversible Pores via Hydrophobic Anchoring of Ionic Amphiphiles

Abstract: Mesoporous silica-based charge reversal systems have gained significant attention in recent years due to a variety of applications such as drug delivery, dye adsorption, catalysis, chromatography, etc. Such systems often use covalent strategies to immobilize functional groups on the silica scaffold. However, lack of dynamism, modularity, and postsynthetic flexibility associated with covalent routes limit their wider applicability. Alternatively, supramolecular routes are gaining increased attention owing to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…During the adsorption process, one‐cycle filtration only took about 10 minutes (Video ). Compared with the performance of other adsorbents that usually required continuously stirring for hours, the adsorption time of α‐MoO 3 flowers for dye removal was much shorter. As a contrast, RhB adsorption by double‐layer untreated carbon cloth was also tested (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…During the adsorption process, one‐cycle filtration only took about 10 minutes (Video ). Compared with the performance of other adsorbents that usually required continuously stirring for hours, the adsorption time of α‐MoO 3 flowers for dye removal was much shorter. As a contrast, RhB adsorption by double‐layer untreated carbon cloth was also tested (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Dyes are very widely used in various industries such as cosmetics, printing and paper [ 18 , 19 ]. Dye removal from wastewater has led to tremendous environmental pollution, which has raised public concern [ 7 , 8 , 9 ]. Nonetheless, defects such as the difficulty of separation exist in the dye removal process when HPU-9 is used as an absorbent.…”
Section: Resultsmentioning
confidence: 99%
“…However, the emission of dyes into the environment has raised widespread public concern relating to water pollution and human health [ 3 , 4 , 5 , 6 ]. Numerous conventional porous materials, such as zeolites, polymeric resins, carbon materials and mesoporous silica, have been considered for dye absorption but exhibit weak selectivity toward targeted dyes and are not cost-effective for practical application [ 7 , 8 , 9 ]. Previous reports have demonstrated that metal-organic frameworks (MOFs) show excellent performances in the recognition capability and selectivity toward a variety of organic dye pollutants because of their tunable chemical functionality, pore microenvironment, structural diversity and high surface areas [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, surface-charge manipulation has gained a lot of consideration because of its prospective use in the area of drug or gene delivery, catalysis, bacterial targeting, separation, sensors, colloidal systems, etc. Extensive researches are being carried out on the fabrication of nanomaterials (NMs) with controlled surface charges to create NMs with the desired characteristics that make materials superior for the appropriate applications. , Consequently, various methods were employed to control the surface charge. These include conditioning of the surface for covalent attachment, electrostatic adsorption at the appropriate pH, switching surface charges by changing the pH, a noncovalent approach, ligand exchange, interaction with polycations, varying the morphology, doping, and ion loading, etc. , Ion loading grabbed more attention because of its control of the postsynthetic surface-charge modification. The added cations or anions using suitable precursors bear intrinsic surface charges and get absorbed onto the material’s surface, which further adjusts the overall surface charge of the system .…”
Section: Introductionmentioning
confidence: 99%